2016
DOI: 10.1177/0267659116649427
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the RemoweLL cardiotomy reservoir for fat and leucocyte removal from shed mediastinal blood: a randomized controlled trial

Abstract: The RemoweLL filter more effectively removed leucocytes from SMB than the Admiral. It offered no advantage in terms of lipid particle clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, some studies found a decrease in fat removal, 75,77 whereas others failed to replicate previous findings. 76 This difference is probably due to a different measurement method. More studies with clinical end points are needed to establish a benefit from this device.…”
Section: Reservoirsmentioning
confidence: 99%
“…However, some studies found a decrease in fat removal, 75,77 whereas others failed to replicate previous findings. 76 This difference is probably due to a different measurement method. More studies with clinical end points are needed to establish a benefit from this device.…”
Section: Reservoirsmentioning
confidence: 99%
“…This result is similar to the findings of Dell’Amore and co-authors 9 and to other studies recently published. 11 In the same way the release of pro-inflammatory cytokines is significantly reduced in Group B (RemoweLL) in contrast with Group A. Unlike the above-mentioned studies we did not register differences between haematocrit, platelets and cholesterol levels; even the release of myocardial necrosis markers looks to be similar.…”
Section: Discussionmentioning
confidence: 40%
“…All continuous data are expressed as mean ± SD. A sample size calculation was carried out to identify the minimum number of patients to be included in each group: on the basis of the studies by Dell’Amore 9 and Lagny and colleagues 11 we would expect a ratio between the mean values relative to the two groups at Time 1 and Time 2 of about 1.25 with a coefficient of variation of 0.25. A two-sided, two-sample t -test with group sample sizes of 21 and 21 achieves 80% power to detect a ratio of 1.250 when the ratio under the null hypothesis is 1.000.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the panel recommends a closed venous reservoir for selected patients to lessen the inflammatory response and enhance biocompatibility. Additionally, considering a separate cardiotomy reservoir may help reduce the adverse effects of shed mediastinal blood, such as fat removal and decreased circulating leukocytes, regardless of the reservoir type [32,33].…”
Section: Reservoirsmentioning
confidence: 99%